A-Type KV Channels in Dorsal Root Ganglion Neurons: Diversity, Function, and Dysfunction - Zemel, Benjamin M.; Ritter, David M.; Covarrubias, Manuel; Muqeem, Tanziyah (Frontiers in Molecular Neuroscience, 2018)
A-type voltage-gated potassium (Kv) channels are major regulators of neuronal excitability that have been mainly characterized in the central nervous system. By contrast, there is a paucity of knowledge about the molecular physiology of these Kv channels in the peripheral nervous system, including highly specialized and heterogenous dorsal root ganglion (DRG) neurons. Although all A-type Kv channels display pore-forming subunits with similar structural properties and fast inactivation, their voltage-, and time-dependent properties and modulation are significantly different. These differences ultimately determine distinct physiological roles of diverse A-type Kv channels, and how their dysfunction might contribute to neurological disorders. The importance of A-type Kv channels in DRG neurons is highlighted by recent studies that have linked their dysfunction to persistent pain sensitization. Here, we review the molecular neurophysiology of A-type Kv channels with an emphasis on those that have been identified and investigated in DRG nociceptors (Kv1.4, Kv3.4, and Kv4s). Also, we discuss evidence implicating these Kv channels in neuropathic pain resulting from injury, and present a perspective of outstanding challenges that must be tackled in order to discover novel treatments for intractable pain disorders.